DIFFERENTIAL IMPACT OF HLA-A, HLA-B AND HLA-DR COMPATIBILITY ON THE RENAL ALLOGRAFT SURVIVAL - V. Y. Abramov; Y. G. Moysyuk; N. N. Kaluzhina; N. B. Bogdanova; V. V. Morozova; N. V. Apanasenko (Вестник трансплантологии и искусственных органов)
We studied the long-term results of 532 deceased donor kidney transplantations to investigate the impact of HLA match on the survival of renal allograft. All transplants were performed in our center in 1996–2009 and moni- tored prospectively for 1–14 years. We found, the survival of 58 kidneys grafted with 0–2 mismatch for HLA- ABDR to be significantly better (Plogrank = 0,016) than the survival of the kidneys grafted with 3–6 HLA-ABDR mismatch. The full compatibility for HLA-A (n = 75) did not influence the long-term survival (Plogrank = 0,48). The absence of HLA-DR mismatch had a beneficial effect for survival of 68 kidneys (Plogrank = 0,07). Eighteen cases with the full HLA-B compatibility between graft and recipient demonstrated excellent long-term survival (Plogrank = 0,007). HLA-B compatibility influenced significantly (P = 0,042) the survival of transplanted kidney in the Cox regression model adjusted for donor and recipient age, panel-reactive antibody level, re-transplant, and immunosuppression protocol. The data obtained support the conclusion, that HLA compatibility should be one of the criteria of deceased donor kidney allocation.